The Implementation of Cooperative Learning Think Pair Share Method to Enhance the Learning Outcomes of Grade VII C Students on Islamic History Material at Darul Istiqomah Bondowoso - Anwar Saeful Basyari, Zen; Nurani, Fahma; ‘Izzati, Dini; Rusiana, Rika (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
The Think Pair Share model provides time for students to think independently, respond to other students, and share with their peers. The implementation of the Think Pair Share model is divided into three stages: Thinking, Pairing, and Sharing, allowing students to actively participate in the learning process and improve learning outcomes. This research was conducted due to the classical and less effective nature of the existing learning process. Student engagement was not maximized, leading to student fatigue and boredom with the course material. The purpose of this research is to improve the understanding and learning outcomes of students in the subject of Islamic History by applying the Think Pair Share cooperative learning model in Grade VII C at Darul Istiqomah Islamic Boarding School in Bondowoso. This study used a classroom action research design conducted in two cycles, with each cycle consisting of two meetings. Data collection techniques included tests, observations, and documentation. The data analysis methods employed were quantitative and qualitative analyses. The results of the study indicated an improvement in students' learning outcomes from Cycle I to Cycle II. The achievement percentage in Cycle I was 56.25%, and after the implementation of Cycle II, it increased by 25% to reach 81.25%. Based on these results, it can be concluded that the application of the Think Pair Share cooperative learning model can enhance students' learning outcomes in the subject of Islamic History at Darul Istiqomah Islamic Boarding School in Bondowoso.